Stylotella Sp. Acetone Extract from Selayar Island and Its Activity against Breast Cancer Cells MCF-7 - Awaluddin Awaluddin; Asriani Ilyas; Firnanelty Firnanelty; Aisyah Aisyah; Andi Nur Fitriani Abubakar; Aisyah Rusdin (Chimica et Natura Acta, 2022)
Styletella sp. is a type of sponge in the Halichondriidae family which is rich in secondary metabolite compounds that have various bioactivities that have the potential as drugs in the future, one of which is anticancer. This study aims to determine the types of secondary metabolites found in Stylotella sp. in Selayar Island and to determine the secondary metabolite bioactivity of MCF-7 breast cancer cells. The method used is extraction using acetone, fractionation and purification. The purity test was carried out by testing three eluent systems at TLC, namely chloroform:ethyl acetate (9:1), n-hexane: acetone (8:2), chloroform: acetone (9:1) eluent. Then qualitatively and characterized by FTIR spectrophotometer. The results showed that pure isolates contained alkaloid compounds. The MCF-7 cell activity test showed an IC50 value for acetone extract of 1452.38 g/mL which has potential anticancer activity and an IC50 value for pure isolate acetone extract of 14983.52 g/mL.